Accounts and accountability in classical Athens - Jones, E (2024)
This thesis examines the phenomenon of accountability in Classical Athens. The Athenians instituted many procedures for examining the conduct of officials, cult personnel, and other individuals. Furthermore, several boards of officials were instructed to inscribe their end-of-year accounts on stone. This study aims (1) to improve our knowledge of the institutional and cultural significance of accountability in the Athenian context, and (2) to explore the link between accountability and the inscription of accounts on stone. Part I fulfils the first objective, Part II the second.